2021
DOI: 10.3390/app11167271
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Acceleration-Based Moving Force Identification Algorithm to Detect Global Bridge Damage

Abstract: This paper presents a new moving force identification (MFI) algorithm that uses measured accelerations to infer applied vehicle forces on bridges. Previous MFI algorithms use strain or deflection measurements. Statistics of the inferred forces are used in turn as indicators of global bridge damage. The new acceleration-based MFI algorithm (A-MFI) is validated through numerical simulations with a coupled vehicle-bridge dynamic interaction model programmed in MATLAB. A focussed sensitivity study suggests that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Solution of equation (20a) can be found acceptable. 95,153 However, first-order regularization approach can be used to further improve the solution as, 151…”
Section: Mfi-based B-wim At a Glancementioning
confidence: 99%
See 2 more Smart Citations
“…Solution of equation (20a) can be found acceptable. 95,153 However, first-order regularization approach can be used to further improve the solution as, 151…”
Section: Mfi-based B-wim At a Glancementioning
confidence: 99%
“…Wang et al 95 came up with a novel acceleration-based MFI algorithm to be used as BHM. It is observed that the equations (20a) and (21) in MFI formulation described earlier, do not take acceleration data as input.…”
Section: Bhm Using Mfi-based B-wimmentioning
confidence: 99%
See 1 more Smart Citation
“…With this framework the process of the bridge's excitation becomes relevantly economical and bridge vibration data is only acquired when the vehicle is on the bridge. Moreover, when vehicles are acting as mobile sensors, the measured responses contain all the spatial information of the target bridge, which significantly improves the condition assessment of bridges [5].…”
Section: Introductionmentioning
confidence: 99%
“…These techniques can be categorised into direct (fixed sensing) or indirect (mobile sensing). Using direct sensing, [5,7] method for bridge damage assessment. Furthermore, in [8,9] the authors utilised the measured rotational response of a bridge under the influence of moving loads for damage assessment.…”
Section: Introductionmentioning
confidence: 99%